HUMAN RESOURCE MANAGEMENT STRATEGY IN IMPROVING THE QUALITY OF EDUCATION - Akmaluddin, Akmaluddin; Kasmini, Lili Kasmini; Sari, Siti Mayang; Iqbal, Muhammad (JURNAL EDUSCIENCE, 2025)
Purpose –Many schools have been established, but national education's effectiveness, efficiency, and quality have not reached the expected standards. To improve the quality of education, school human resource management must be renewed through school reconstruction.Methodology –This research method is qualitative and uses a case study framework. Data collection methods include direct observation of school management activities, comprehensive interviews with stakeholders such as teachers, principals, and educators, and examination of documents related to the curriculum used.Findings –The research findings show that human resource planning is arranged regularly by school autonomy, the organization is carried out by segmenting work systems, work programs, and HR development, training, and career development have a positive effect on schools and their staff, Compensation is determined by considering direct and indirect provision models, Performance evaluation is carried out through two dimensions, namely teacher performance evaluation and school performance evaluation.Significance –Human resource management can improve the quality of education at State Elementary School 25 Banda Aceh and internal and external customer satisfaction, and it can be categorized as good.